As abreviaturas na escrita setecentista: pistas gráficas como recurso subsidiário de caracterização sociolinguística do escrevente - Vivian Canella Seixas (2020)
This research object was the use of abbreviations in eighteenth century private letters written in Portuguese Language. This choice is justified not only by the fact that it is a relatively unexplored subject of study, but also because the results achieved, if the hypothesis presented here, can make a relevant contribution to linguistic studies, especially of a methodological nature, and then expand the possibilities of using past documents whose scribes sociolinguistic data are unknown. In this context, the main hypothesis raised was that such resources may highlight the social aspects of the scribe of past periods, thus allowing their sociolinguistic characterization. To test it, we adopted the Language Variation and Change Theory (LABOV, 2008 [1972]) regarding the data selection, collection and analysis. The corpus is composed of 24 personal letters from the second half of the eighteenth century written in the Portuguese Language of Brazil and the European Language by men and women of higher social class and lower social class and come from two sources: (i) from Fundo Barão de Camargos collection, of the Historical Archive of the Museu of the Inconfidência, and (ii) from the project Post Scriptum: A Digital Archive of Ordinary Writing (Early Modern Portugal and Spain), of the Linguistics Center of the University of Lisbon. The results showed that (i) there was a norm of use of brachygraphic resources in the 18th century and some of its rules demanded formal knowledge; (ii) writers with a higher level of education had mastery of the employment rule of brachygraphic resources and employed both more general resources and more specific rules; (iii) the external variables education level, socioeconomic status and gender and the internal variables typology, rule complexity, number of syllables of abbreviated words and word class interfered with the use of abbreviations; thus (iv) these resources translate linguistic and extralinguistic information about the one behind the pen and, consequently, are a methodological tool to assist in its sociolinguistic characterization.